Prevalence and factors associated with poor performance in the 5‐chair stand test: findings from the Cognitive Function and Ageing Study II and proposed Newcastle protocol for use in the assessment of sarcopenia. Issue 2 (18th January 2021) - Dodds, Richard Matthew; Murray, James C.; Granic, Antoneta; Hurst, Christopher; Uwimpuhwe, Germaine; Richardson, Sarah; Brayne, Carol; Matthews, Fiona E.; Sayer, Avan A.; ,
Abstract: Background: Poor performance in the 5‐chair stand test (5‐CST) indicates reduced lower limb muscle strength. The 5‐CST has been recommended for use in the initial assessment of sarcopenia, the accelerated loss of muscle strength and mass. In order to facilitate the use of the 5‐CST in sarcopenia assessment, our aims were to (i) describe the prevalence and factors associated with poor performance in the 5‐CST, (ii) examine the relationship between the 5‐CST and gait speed, and (iii) propose a protocol for using the 5‐CST. Methods: The population‐based study Cognitive Function and Ageing Study II recruited people aged 65 years and over from defined geographical localities in Cambridgeshire, Newcastle, and Nottingham. The study collected data for assessment of functional ability during home visits, including the 5‐CST and gait speed. We used multinomial logistic regression to assess the associations between factors including the SARC‐F questionnaire and the category of 5‐CST performance: fast (<12 s), intermediate (12–15 s), slow (>15 s), or unable, with slow/unable classed as poor performance. We reviewed previous studies on the protocol used to carry out the 5‐CST. Results: A total of 7190 participants aged 65+ from the three diverse localities of Cognitive Function and Ageing Study II were included (54.1% female). The proportion of those with poor performance in the 5‐CST increased with age, from 34.3% at age 65–69 to 89.7% at age 90+. Factors independently associated with poor performance included positive responses to the SARC‐F questionnaire, physical inactivity, depression, impaired cognition, and multimorbidity (all P  < 0.005). Most people with poor performance also had slow gait speed (57.8%) or were unable to complete the gait speed test (18.4%). We found variation in the 5‐CST protocol used, for example, timing until a participant stood up for the fifth time or until they sat down afterwards. Conclusions: Poor performance in the 5‐CST is increasingly common with age and is associated with a cluster of other factors that characterize risk for poor ageing such as physical inactivity, impaired cognition, and multimorbidity. We recommend a low threshold for performing the 5‐CST in clinical settings and provide a protocol for its use.